Service quality of Banking sectors in Morang district of Nepal (TUTA Journal, 2022)
This paper assesses the service quality in banking sectors in Morang district of Nepal based on different levels of customers’ perception regarding service quality. Today customers’ expectation are rising competitively due to many players are in the ground. Customer is the first rating group in the Nepalese banking Sectors.